Measuring the Impact of Social Media on Brand Trust A Case Study of Virgin Media - Draganoiu, Sandra-Madalina (2011)
With scant literature on Social Media and brand trust influenced through the online environment, I have decided to conduct a research based on this theme. Although ethnography would have been a more appropriate methodology, because of certain limitations, two methods of research will be used: semi structured interviews with key employees from Virgin Media and an online survey ran through the customers of Virgin Media. The interviews have given a better understanding of the company’s culture and how they view and use Social Media. Several themes were identified through the interviews and then, with the help of the survey, i could see if the strategy Virgin Media is implementing is actually reaching the customers and having the desired result. With the help of the survey, a brand trust scale will also be developed and several items from it will be crucial in its development. The Online Marketing sector from Virgin Media is strictly connected with the Customer Service one, thus giving them a better coverage of the customer feedback and a better understanding of what impact Social Media has on them. Although some of the channels Virgin Media are using (e.g. Facebook) have been recently set up, customers seem pleased with their management and feel they can trust Virgin Media through these channels.